2022
DOI: 10.1161/circulationaha.121.057599
|View full text |Cite
|
Sign up to set email alerts
|

Histone Acetyltransferases p300 and CBP Coordinate Distinct Chromatin Remodeling Programs in Vascular Smooth Muscle Plasticity

Abstract: Background: Vascular smooth muscle cell (VSMC) phenotypic switching contributes to cardiovascular diseases. Epigenetic regulation is emerging as a key regulatory mechanism, with the methylcytosine dioxygenase TET2 acting as a master regulator of smooth muscle cell phenotype. The histone acetyl-transferases p300 and CREB-binding protein (CBP) are highly homologous and often considered to be interchangeable, and their roles in smooth muscle cell phenotypic regulation are not known. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 39 publications
2
31
0
Order By: Relevance
“…HDAC hyperactivity is a hallmark of cancer and promotes cell proliferation. Recently, Chakraborty et al, demonstrated, using VSMC-specific knockout mice, that p300 and TET2 are mutually required to stimulate the expression of contractile markers, while CBP facilitates the recruitment of HDAC2 and 5 to contractile protein promoters to lock the chromatin ( Chakraborty et al, 2022 ).…”
Section: Vascular Smooth Muscle Cellsmentioning
confidence: 99%
“…HDAC hyperactivity is a hallmark of cancer and promotes cell proliferation. Recently, Chakraborty et al, demonstrated, using VSMC-specific knockout mice, that p300 and TET2 are mutually required to stimulate the expression of contractile markers, while CBP facilitates the recruitment of HDAC2 and 5 to contractile protein promoters to lock the chromatin ( Chakraborty et al, 2022 ).…”
Section: Vascular Smooth Muscle Cellsmentioning
confidence: 99%
“…Similarly, Tet2 deficiency in Ldl receptor null mice fed a high fat diet leads to markedly accelerated atherosclerosis that can be rescued by NLRP3 inhibition [49]. Tet2 is also a master regulator of vascular smooth muscle cell plasticity and Tet2 activation also promotes vascular smooth muscle proliferation and intimal hyperplasia, which may further contribute to accelerated atherosclerosis [50][51][52][53][54].…”
Section: Molecular Mechanisms Of Ch-mediated Cardiotoxicitymentioning
confidence: 99%
“…Alternatively, leveraging epigenetic and pharmacological agents that target key signaling pathways controlling inflammation and SMC phenotype, rather than directly altering cytokines and chemokines, might be a viable approach to maintain the differentiated phenotype of SMCs in atherosclerosis. [22][23][24] The dual recombinase lineage tracing system demonstrated here by Owsiany et al 11 offers a unique tool to dissect gene regulatory networks controlling the function and phenotype of Lgals3-transitioned SMCs. With minor modifications, this model can be utilized in the study of other subpopulations of SMCs with high specificity.…”
Section: See Accompanying Article On Page 942mentioning
confidence: 99%